Recognizing Hijaiyah Letters Through Letter Tree Media For Early Childhood Of 5 - 6 Years Old - Sriastuti, Iin; Zulkarnaen, Zulkarnaen (Universitas Muhammadiyah Ponorogo, 2023)
This Classroom Action Research (CAR) was conducted on the basis of a lack of understanding and recognition of hijaiyah letters which were still lacking in group B1 RA Taqiyya. This is because the media used is less creative and innovative. For this reason, the researcher uses the Hijaiyah Letter Tree media to improve the ability to read and recognize Hijaiyah letters. The subjects in this study were the Tiger B1 RA Taqiyya Group, which consisted of 12 children, 5 boys and 7 girls. This type of research is class action research (Class Action Research) which consists of two cycles carried out in 4 meetings for each cycle. Research procedures include planning, implementing, observing, and reflecting. In using hija'iah letter tree media to improve children's reading skills, it is recommended that a teacher should prepare things that support the implementation of learning using interesting letter tree media in accordance with the stages of development and the needs of children. The results showed that the use of the Hijaiyah Letter Tree media could increase the ability to recognize Hijaiyah letters for children which is 86%.